Successful Strategies for Engaging Chinese Breast Cancer Survivors in a Randomized Controlled Trial - Wu, Christine S. (Transl Issues Psychol Sci, 2019)
Chinese immigrant breast cancer survivors face various challenges due to cultural and socioecological factors. Research efforts to develop culturally sensitive interventions have been limited by lack of knowledge regarding successful recruitment and implementation practices among Chinese immigrant populations. This paper documents strategies utilized during the development and implementation of a randomized controlled trial of a culturally sensitive psychosocial intervention for Chinese immigrant breast cancer survivors. In partnership with a community agency, we developed culturally and linguistically appropriate research materials, recruited participants from community channels, and conducted longitudinal data collection. Key strategies include building equitable research partnerships with community agencies to engage participants; being responsive to the needs of community agencies and participants; considering within-group diversity of the research population; utilizing recruitment as an opportunity for relationship-building with participants; and developing key strategies to promote retention. Successful participant engagement in cancer intervention research is the result of collaboration among breast cancer survivors, community leaders and agencies, and academic researchers. The engagement process for this study is novel because we have emphasized cultural factors in the process and taken a relational approach to recruitment and retention.